Hybrid Heuristic for the Inventory Location-Routing Problem - Guerrero, W.J.; Prodhon, C.; Velasco, N.; Amaya, C.A. (Elsevier B.V., 2013)
Resolver el problema de localización y ruteo de inventarios optimiza simultáneamente el diseño de la cadena de suministro y sus costos operacionales. Los supuestos del modelo incluyen el hecho que los vehículos pueden visitar más de un cliente por ruta y se incluyen las decisiones de inventario para un sistema con múltiples depósitos, con múltiples puntos de venta para un horizonte de planeación discreto. El problema es determinar el conjunto de depósitosporabrir, las cantidades por enviar desde los proveedores a los depósitos y de los depósitos a los puntos de venta, y la secuencia en que los puntos de venta serán visitados por una flota de vehículos homogénea. Un modelo de programación entera-mixta se propone para describir el problema. Un método hibrido que involucra un enfoque exacto dentro de un esquema heurístico es presentado. Su desempeño se prueba con instancias del problema de localizacion y ruteo, y de ruteo de inventarios.

Solving the Inventory Location-Routing Problem can been seen as an approach to optimize both a supply chain design and its operations costs. Assumptions consider that vehicles might visit more than one retailer per route and that inventory management decisions are included for a multi-depot, multi-retailer system with storage capacity over a discrete time planning horizon. The problem is to determine the set of candidate depots to open, the quantities to ship from suppliers to depots and from depots to retailers per period, and the sequence in which retailers are replenished by an homogeneous capacitated fleet of vehicles. A mixed-integer linear programming model is proposed to describe the problem. Since the model is not able to solve exactly the targeted instances within a reasonable computation time, a hybrid method, embedding an exact approach within a heuristic scheme, is presented. Its performance is tested over instances for the inventory location routing, location-routing and inventory-routing problems.
Keywords: Control de la producción; Production control; Control de inventarios; Inventory control; Logística empresarial; Business logistics; Location-Routing Problem; Inventory-Routing Problem; Hybrid Heuristic; Combinatorial Optimization